The meta-policy information base. - Polyrakis, A.
The growth of computer networks has revealed significant scalability and efficiency limitations to the traditional management techniques. Policy-based networking (PBN) has emerged as a promising paradigm for configuration management and service provisioning. The common open policy service (COPS) and its extension for policy provisioning (COPS-PR) are currently being developed as the protocols to implement PBN. COPS-PR has received significant attention and seems efficient for several management areas. However, the rigidity of its policy-enforcing mechanisms constrains the intelligence that can be pushed toward the managed devices. This work aims at relaxing this limitation by using meta-policies, rules that enforce the appropriate policies on the devices. Meta-policies are stored and processed by the devices, independent of their semantics, thus making the model more efficient, scalable, distributed, and robust. The additional functionality is implemented through a novel policy information base we have defined, the meta-policy PIB
Keywords: COPS; COPS-PR.; PBN; Common open policy service; Computer networks; Configuration management; Efficiency; Functionality; Managed devices; Management techniques; Meta-policy PIB; Meta-policy information base; Policy provisioning; Policy-based networking; Policy-enforcing mechanisms; Scalability; Service provisioning